2009
DOI: 10.1038/nrrheum.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Management of cardiovascular disease risk in chronic inflammatory disorders

Abstract: Patients with chronic inflammatory disorders are at increased risk of developing premature cardiovascular disease. Despite significant advances in our understanding of the effects of inflammatory pathways on the vasculature, clear guidelines on the management of traditional and nontraditional cardiovascular risk factors in patients with systemic autoimmunity are lacking. Thus, rigorous studies assessing the individual contributions of the various treatments used in autoimmune disorders, as well as their effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 136 publications
(125 reference statements)
0
56
0
2
Order By: Relevance
“…The degree of inflammation, as assessed by high sensitivity CRP, cytokines or antineutrophil cytoplasmic antibodies (ANCA) also predicts cardiovascular mortality and morbidity [1]. These observations suggest that arterial stiffness and cardiovascular mortality and morbidity should be increased in subjects with systemic inflammation [24][25][26][27][28][29][30][31][32][33][34]. However, some data concerning this are conflicting [35].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of inflammation, as assessed by high sensitivity CRP, cytokines or antineutrophil cytoplasmic antibodies (ANCA) also predicts cardiovascular mortality and morbidity [1]. These observations suggest that arterial stiffness and cardiovascular mortality and morbidity should be increased in subjects with systemic inflammation [24][25][26][27][28][29][30][31][32][33][34]. However, some data concerning this are conflicting [35].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, it has become evident that upregulation of inflammation and autoimmune aggression in certain systemic disorders such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) may substantially accelerate atherogenesis and increase the risk of vascular events [10][11][12]. Basic and clinical research studies in this *Address correspondence to this author at the Boğaziçi University, Department of Molecular Biology and Genetics, 34342 Bebek/Istanbul, Turkey; Tel: +90(212) 359-77-84; Fax: +90 (212) 287-2468; E-mail: sahru.yuksel@boun.edu.tr field have led to the emergence of a new biomedical discipline, vascular rheumatology [13], which aims to clarify pathophysiology of rheumatic diseases and co-morbidities and to propose recommendations for primary and secondary prevention of vascular events in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…31 Several studies have revealed that atherogenesis is highly accelerated by upregulated inflammation and autoimmune attacks in highgrade inflammatory disorders such as rheumatoid arthritis and SLE. 32,33 Relationship between atherogenesis and low-grade inflammatory conditions such as ankylosing spondylitis and FMF has been relatively recently suggested and studies about this relationship build up over time. [34][35][36] However, studies investigating carotid atherosclerosis in FMF found less aggressive course of atherogenesis than atherogenesis in highgrade inflammatory disorders.…”
mentioning
confidence: 99%